2018
DOI: 10.1186/s12941-018-0259-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of next-generation sequencing to characterize novel mutations in clarithromycin-susceptible Helicobacter pylori strains with A2143G of 23S rRNA gene

Abstract: BackgroundClarithromycin (CLR) resistance has become a predominant factor for treatment failure of Helicobacter pylori eradication. Although the molecular mechanism of CLR resistance has been clearly understood in H. pylori, it is lack of evidence of other genes involved in drug resistance. Furthermore, the molecular mechanism of phenotype susceptible to CLR while genotype of 23S rRNA is mutant with A2143G is unclear. Here, we characterized the mutations of CLR-resistant and -susceptible H. pylori strains to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…A study in adults from the same district in Zhejiang Province showed that all of phenotype-resistant strains (n=6) presented mutation A to G at position 2143 of the 23S rRNA, while 2 mutant-type of 23S rRNA gene at position 2143 (A>G) was also detected in sic phenotype-susceptible strains. 22 Another study in adults from the same area showed that 90.4% gene mutations of the 23S rRNA were the A2143G mutation. 23 H. pylori strains were found to carry A2143G, A2142G, A2147G and A2146G mutations that can lead to clarithromycin-resistance in Africa, Asia, South America, Europe and North America.…”
Section: Discussionmentioning
confidence: 97%
“…A study in adults from the same district in Zhejiang Province showed that all of phenotype-resistant strains (n=6) presented mutation A to G at position 2143 of the 23S rRNA, while 2 mutant-type of 23S rRNA gene at position 2143 (A>G) was also detected in sic phenotype-susceptible strains. 22 Another study in adults from the same area showed that 90.4% gene mutations of the 23S rRNA were the A2143G mutation. 23 H. pylori strains were found to carry A2143G, A2142G, A2147G and A2146G mutations that can lead to clarithromycin-resistance in Africa, Asia, South America, Europe and North America.…”
Section: Discussionmentioning
confidence: 97%
“…Quek et al revealed that A2143G and T2182C genotypes were detected not only in resistant isolates but also in clarithromycin-susceptible strains [31]. Chen et al isolated two clarithromycinsusceptible H. pylori strain with mutation A2143G of the 23S rRNA gene [15].…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori was identified based on colony morphology (small and translucent colonies) and typical appearance on Gram stain as a gull wing-shape bacteria and also by positive reactions for oxidase, catalase, and strong urease activity. After subculturing on Columbia agar, all of them were stored in brain heart infusion broth with 30% glycerol and 7% FCS at −70°C [15,16].…”
Section: H Pylorimentioning
confidence: 99%
“…Several of these already stand out as interesting proteins. HPG27_715 encodes for a multi drug and toxic compound extrusion (MATE)type multidrug efflux pump (Chen, Ye et al 2018). Inactivation of gene HPG27_715 significantly decreased biofilm formation.…”
Section: Discussionmentioning
confidence: 99%